The Impact of Macroeconomic Indicators on Stocks Returns for the Jordanian Insurance Companies during the Period (2000 a 2012) (Global Journal of Management and Business Research, 2014)
Abstract not found
Keywords: macroeconomic indicators; stock returns; jordanian insurance companies